Faktor-Faktor Yang Mempengaruhi Kejadian TB Paru Di Wilayah Kerja Puskesmas Pamenang Tahun 2021 - Isra Miharti (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2022)
Tuberculosis is still a public health problem that is a challenge. Global Tuberculosis is an infectious disease caused by Mycobacterium Tuberculosis, Tuberculosis remains the top 10 cause of death in the world and Tuberculosis deaths globally are estimated at 1.3 million patients.  Tuberculosis (TB) is still a health problem in the world, although control efforts with the Directly Observed Treatment Shortcourse (DOTS) strategy have been implemented in many countries since 1995.This type of research is a quantitative study with a cross sectional approach, this research was conducted in the work area of ​​the Pamenang Health Center in 2021. The population in this study was 35 people who were registered in the pulmonary TB registration book, and as a control of all neighbors with pulmonary TB as many as 35 people. The results of this study indicate that it is known from 70 houses that were observed to have good knowledge 47 (67.2%) sufficient knowledge 15 (21.4%) less 8 (11.4%), which have low economic status 64 (91.4%), high economic status 6 (8.6%) of the 70 houses were observed, 26 (37.1%) houses had inappropriate humidity and 44 (62.9%) houses had suitable humidity. There is no relationship between knowledge, economic status with the incidence of pulmonary TB and there is a relationship between humidity and the incidence of pulmonary TB in the work area of ​​the Pamenang Health Center in 2021. It is recommended that the Pamenang Health Center provide counseling to the community regarding the relationship between humidity and the incidence of pulmonary TB.